Integrated AI FP&A: Unlocking the Highest Stage of FP&A Maturity - Anna Chekashova (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This paper outlines a detailed roadmap for achieving the Leading stage of FP&A maturity, as defined by the FP&A Trends Group (2023), and introduces Integrated AI FP&A as its natural evolution. As organizations face accelerated decision cycles, rising operational complexity, and increasing ESG demands, traditional planning models are no longer sufficient. Enterprises require planning systems that are real-time, transparent, and continuously adaptive, capable of enabling dynamic scenario analysis, cross-functional collaboration, and strategic agility. The proposed transformation framework is structured around six interdependent pillars: strategy alignment, governance, process redesign, modular architecture, data integration, and cultural change. Together, these enable real-time forecasting, shared forecast ownership, and convergence of ESG and financial metrics across business units. At its core, Integrated AI FP&A is a modular, AI-enabled planning environment that extends Leading-stage capabilities into an autonomous, signal-responsive operating model. This architecture supports rolling forecasts, automatic scenario switching, and real-time planning adjustments based on live operational inputs. By embedding machine learning, API-triggered data orchestration, and ESG-calibrated forecast logic, Integrated AI FP&A transforms finance from a retrospective reporting function into a forward-looking, intelligent decision-support system. This paper presents a concrete, scalable system architecture for implementing Integrated AI FP&A at the enterprise level, bridging strategy and operations through real-time data and autonomous financial logic. Integrated AI FP&A closes the gap between strategic objectives and operational execution, reimagining the finance function as a real-time performance command center that empowers CFOs to drive faster decisions, build resilience, and increase enterprise value.